Regional adaptation measures to minimise climate risks in agriculture - S. A. Teymurov; M.-R. A. Kaziev; A. A. Bagomaev (Юг России: экология, развитие)
Aim. Definition of a set of regional adaptation measures to reduce the negative effects of climate risks in agriculture in Dagestan.The research material was the collection and processing of climate change data gathered during the ERA5 programme (atmospheric reanalysis of the global climate of the fifth generation ECMWF, covering the time range from 1979 to 2022 with a spatial resolution of 30 km). Analytical works, scientific research on risk assessment and adaptation of agriculture, and analysis of the current state and resource potential of soils of arid ecosystems of the Dagestan plain zone were used in this study.In the Republic of Dagestan, data on the cyclical nature of climate change can be observed, starting in 1979. From 1979 to 2022, the annual change in average temperature increased by 2.8 °C (trend line by 2.3 °C), while the average precipitation decreased by 173.4 mm (trend line by 196.3 mm). In analysing the increase in the degree of aridity and the extinction of the hydromorphic regime of soil formation, five ecological groups were identified according to the degree of degradation in order to develop a strategy to minimise the climatic risks of the Dagestan lowland (plain) zone: lands of good, satisfactory, mediocre, poor and very poor agroecological condition. Adaptation measures to minimize climate risks in the agricultural sector are proposed.Adaptation measures necessary to manage natural and environmental risks to climate change should meet modern requirements for sustainable agriculture and contribute to the improvement of agricultural production.